Pengalaman ibu post partum tentang perawatan luka perineum dalam perspektif budaya - Ulfah, Diana; Marlina, Yani; Tambunan, Irisanna (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2024)
Background: The post partum period is an important period for mothers because perineal wound care plays a crucial role in recovery. Cultural beliefs and values ​​often influence maternal compliance with medical education. Many mothers still choose traditional practices, such as the use of herbal concoctions or restricted bathing, which sometimes conflict with medical standards. Understanding post partum mothers' experiences of perineal wound care from a cultural perspective is important for a scientifically based, culturally sensitive care approach. Purpose: To explore the experiences of post partum mothers in caring for perineal wounds and provide an understanding of how to care for these wounds which is influenced by local culture. Apart from that, to broaden nurses' horizons to better appreciate cultural values ​​in society and be able to provide appropriate education regarding perineal wound care. Method: The research design uses a descriptive qualitative phenomenological approach. The informants taken in this research were 6 post partum mothers who were carried out in the independent practice of midwives in the Cileunyi Kulon sub-district area in September - November 2024. The data analysis in this study used the Collaizzi method which has simple, systematic and detailed stages. Results: Beliefs influence mothers' compliance with health education and mothers often prefer traditions. The use of herbal concoctions and activity restrictions dominate wound care so that the family's role is to provide support and advice, thereby influencing treatment decisions. Conclusion: Culture influences post partum mothers' compliance with medical education. There are still many mothers who choose traditional practices in treating perineal wounds. Three main themes were found, namely the influence of culture on compliance, culturally based perspectives on perineal wound care, and the role of family and community. Suggestion: Further research is needed to explore the influence of culture on maternal compliance in perineal wound care.   Keywords: Culture; Perineal Wound Care; Post partum Mothers.   Pendahuluan: Masa post partum adalah periode penting bagi ibu karena perawatan luka perineum memegang peran krusial dalam pemulihan. Kepercayaan dan nilai-nilai budaya sering memengaruhi kepatuhan ibu terhadap edukasi medis. Banyak ibu masih memilih praktik tradisional, seperti penggunaan ramuan herbal atau pembatasan mandi yang kadang bertentangan dengan standar medis. Pemahaman tentang pengalaman ibu post partum dalam perawatan luka perineum dari perspektif budaya penting untuk pendekatan keperawatan peka budaya berbasis ilmiah. Tujuan: Untuk menggali pengalaman ibu post partum dalam merawat luka perineum dan memberikan pemahaman tentang cara merawat luka tersebut yang dipengaruhi oleh budaya setempat. Selain itu untuk memperluas wawasan perawat untuk lebih menghargai nilai-nilai budaya di masyarakat serta mampu memberikan edukasi yang tepat mengenai perawatan luka perineum. Metode: Desain penelitian menggunakan pendekatan deskriptif kualitatif fenomenologi. Informan yang diambil dalam penelitian ini adalah 6 orang ibu post partum yang dilaksanakan di praktek mandiri bidan wilayah kelurahan Cileunyi Kulon pada bulan September - November 2024. Adapun analisa data pada penelitian ini menggunakan metode Collaizzi yang memiliki tahapan sederhana, sistematis, dan rinci. Hasil: Kepercayaan memengaruhi kepatuhan ibu terhadap edukasi kesehatan dan seringkali ibu lebih memilih tradisi. Penggunaan ramuan herbal dan pembatasan aktivitas mendominasi perawatan luka sehingga peran keluarga adalah memberi dukungan dan nasihat sehingga memengaruhi keputusan perawatan. Simpulan: Budaya mempengaruhi kepatuhan ibu post partum terhadap edukasi medis. Masih banyak ibu yang memilih praktik tradisional dalam perawatan luka perineum. Tiga tema utama ditemukan yaitu pengaruh budaya terhadap kepatuhan, perspektif perawatan luka perineum berbasis budaya, dan peran keluarga serta komunitas. Saran: Penelitian lebih lanjut diperlukan untuk menggali pengaruh budaya terhadap kepatuhan ibu dalam perawatan luka perineum.   Kata Kunci: Budaya; Ibu Post Partum; Perawatan Luka Perineum